تعليم اللغة العربية لأغراض خاصة في ماليزيا: دراسات وتطبيقات - Chik, Abdul Rahman (King Abdullah bin Abdul Aziz International Center for Arabic Language, Riyadh, Saudi Arabia., 2017)
The chapter discusses Teaching Arabic for Specific Purposes (TASP) in Malaysia, historical background, Scope, models of TASP, samples of lesson planning, with examples.